-33=-11*3
-8=-11+3
so
(x-11)(x+3)
<em>Answer:</em>
<em>1cm = 50
</em>
<em>2 cm = 50 x 2
</em>
<em>3cm = 50 x 3
</em>
<em>and the inverse:50m = 50/50 = 1cm
</em>
<em>100m = 100/50 = 2cm
</em>
<em>150m = 150/50 = 3cm
</em>
<em>381m = 381/
</em>
Answer:
$7
Step-by-step explanation:
Your two equations are ...
Double the second equation and subtract the first:
2(2s +4t) -(4s +6t) = 2(42) -(70)
2t = 14 . . . . . simplify
t = 7 . . . . . . . divide by 2
The cost of each tie is $7.
Answer:
(-65)/17
Step-by-step explanation:
Evaluate 3/(x - 2) - sqrt(x - 3) where x = 19:
3/(x - 2) - sqrt(x - 3) = 3/(19 - 2) - sqrt(19 - 3)
19 - 3 = 16:
3/(19 - 2) - sqrt(16)
19 - 2 = 17:
3/17 - sqrt(16)
sqrt(16) = sqrt(2^4) = 2^2:
3/17 - 2^2
2^2 = 4:
3/17 - 4
Put 3/17 - 4 over the common denominator 17. 3/17 - 4 = 3/17 + (17 (-4))/17:
3/17 - (4×17)/17
17 (-4) = -68:
3/17 + (-68)/17
3/17 - 68/17 = (3 - 68)/17:
(3 - 68)/17
3 - 68 = -65:
Answer: (-65)/17